STATE CONTROL AND SUPERVISION IN THE FIELD OF ROAD TRAFFIC SAFETY OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2025)
The authors chose one of the most relevant modern topics on ensuring safety in the field of road traffic. In August 2024, 141.5 thousand units of motor vehicles were registered, an increase of 44.1% compared to the same period last year. As of September 1, 2024, the number of registered motor vehicles in Kazakhstan amounted to 5,579.4 thousand units, of which 88% were passenger cars, 9.9% were trucks and 2.1% were buses.In this regard, a special role here is assigned to the state, which carries out Control and supervision of road traffic security through the adoption of related legal norms that ensure not only road traffic, but also spheres of Public Relations.In this article, the authors considered some of the reasons for the occurrence of a road accident, the competencies of some state bodies to ensure road traffic, as well as regulatory legal acts establishing the legal basis and functioning of road traffic in the Republic of Kazakhstan and ensuring its safety.In addition, the authors studied significant international and foreign scientific research on the problems of road safety and ways to solve them.Keywords: Regulatory legal acts in the field of road safety, problems of road safety, state control and supervision, traffic, traffic accidents, national security, road safety.